SupPhreeqc: A program for generating customized Phreeqc thermodynamic datasets from Supcrtbl and extending calculations to elevated pressures and temperatures. (October 2020) - Zhang, Guanru; Lu, Peng; Zhang, Yilun; Tu, Kevin; Zhu, Chen
Abstract: Supcrt and Phreeqc are two software packages widely used for thermodynamic calculations and geochemical modeling of gas-water-mineral reactions, respectively. The versatility and easy-to-use functions of Phreeqc have earned its popularity, but the software is limited by the default thermodynamic datasets it is distributed with, which has limited Phreeqc applications to mostly at ambient temperature. To expand the applicability of Phreeqc to wider temperature and pressure conditions, this study developed the software utility SupPhreeqc that extracts thermodynamic data from Supcrtbl and translates them into Phreeqc -readable formats. By linking Supcrtbl and Phreeqc, this study helps harness high-quality thermodynamic data for minerals and a large number of inorganic and organic aqueous species with the Helgeson-Kirkham-Flowers equation of state parameters for speciation and solubility modeling at elevated T-P . SupPhreeqc can generate both formats of Phreeqc datasets, namely, phreeqc.dat and llnl.dat . These two formats differ in activity coefficient and gas-mixing models, as well as pressure corrections for log K . As examples, three datasets were made from SupPhreeqc : diagenesis.dat (0.01–200 °C and up to 1000 bar), geothermal.dat (0.01–300 °C at P SAT ), and bl.dat at 0.5, 1, 2, and 5 kb 1000 °C. The diagenesis.dat and geochermal.dat datasets have also incorporated the library of callable BASIC scripts for rate equations and kinetic parameters for 53 minerals. These databases can be downloaded or run together with Phreeqc online at https://models.earth.indiana.edu . Highlights: SupPhreeqc links two geochemical programs Phreeqc and Supcrtbl . Enabling geochemical modeling for carbon sequestration, diagenesis, and geothermal systems. Take in the high-quality thermodynamic data and generate databases at customized T-P conditions. diagenesis.dat with a T-P grid of 0.1–200 °C with pressure up to 1 kb and non-ideal gas mixing. geothermal.dat with T-P grid of 0–300 °C at Psat and bl.dat up to 1000 °C and 5000 bars.